Glucosamine HCl-based solid dispersions to enhance the biopharmaceutical properties of acyclovir. - Darshan R. Telange; Snehal B. Bhagata; Arun T. Patila; Milind J. Umekara; Anil M. Petheb; Nishikant A. Raut; Vivek S. Dave (Journal of Excipients and Food Chemicals, 2024)
The objective of the work presented here was to assess the feasibility of using glucosamine HCl as a solid-dispersion (SD) carrier to enhance the biopharmaceutical properties of a BCS class III/IV drug, acyclovir (ACV). The solid-dispersions of acyclovir and glucosamine HCl were prepared by an ethanol-based solvent evaporation method. The prepared formulations characterized by photomicroscopy, scanning electron microscopy (SEM), differential scanning calorimetry (DSC), Fourier transforms infrared spectrophotometry (FTIR), powder x-ray diffractometry (PXRD) and drug content analysis. The functional characterization of ACV-SD was performed by aqueous solubility evaluation, dissolution studies, fasted versus fed state dissolution comparison, ex vivo permeability, and stability studies. Photomicroscopy and SEM analysis showed different surface morphologies for pure ACV, glucosamine HCl and ACV-SD. The physical-chemical characterization studies supported the formation of ACV-SD. A 12-fold enhancement in the aqueous solubility of ACV was observed in the prepared solid dispersions, compared to pure ACV. Results from in vitro dissolution demonstrated a significant increase in the rate and extent of ACV dissolution from the prepared ACV-SD formulations, compared to pure ACV. The rate and extent of ACV permeability across everted rat intestinal membrane were also found to be significantly increased in the ACV-SD formulations. Under fed conditions, the rate and extent of the in vitro dissolution of ACV from the formulation was appreciably greater compared to fasted conditions. Overall, the results from the study suggest the feasibility of utilizing glucosamine HCl as a solid dispersion carrier/excipient for enhancement of biopharmaceutical properties of acyclovir, and similar drugs with low solubility/permeability characteristics.